O conhecimento pedagógico de conteúdo de Química: caracterização de obstáculos epistemológicos na concepção de licenciandos em Química - Pena, Graziele Borges de Oliveira (2018)
The exercise of teaching activity, whether in the field of Chemistry or in other areas, has undergone several challenges, among them, the lack of social recognition of this profession and the teacher's difficulty in modifying teaching practices and adapting them to the current needs, such as training critical citizens who are able to act effectively in society. These challenges permeate the professionalization process of the teaching career, which is a complex theme and involves many elements. Without underestimating the importance of these other elements, but, understanding the importance of legitimizing the building process of teaching professional knowledge as a decisive factor of professional distinction, this legitimation depends on several factors to promote a changing process in the way of teaching Chemistry. Among them, efforts to understand what can obstruct, in terms of difficulties/barriers, the development of a specific professional knowledge of chemistry teachers. In this perspective is the objective of this research, which aims to deepen the understanding about the specific professional knowledge for teaching in Chemistry characterizing this knowledge as well as characterizing obstacles of an epistemological nature in the conception of graduates in Chemistry related to the construction of the knowledge inherent to the teaching professionalization. The investigative work was structured in two ways. The first, of theoretical bias, led us to propose a specific knowledge construct for teaching in Chemistry - Pedagogy Content Knowledge Chemistry (PCKC), a specific knowledge base to teach Chemistry and ways to develop PCKC. In the second methodological way, from the participant observation, the application of questionnaire and semi-structured interview with a group of graduates of the last periods of a degree in Chemistry at Federal University of Mato Grosso - University Campus of Araguaia - we used the Discursive Textual Analysis to identify the conceptions of future professors of Chemistry and to characterize difficulties and/or impediments for the development of the specific professional knowledge for teaching in Chemistry. We identified and characterized two epistemological obstacles: experiential obstacle and value obstacle. The characterization of these obstacles and the understanding of their implication in the process of developing the specific professional knowledge in chemistry by the teacher can contribute to improve the initial teacher training and perhaps provide ways to change the way Chemistry is taught. In addition, the deepening and understanding provided by the research on the specific professional knowledge in teaching Chemistry, in terms of theoretical proposition of the specific knowledge construct for Teaching in Chemistry (PCKC), a specific knowledge base to teach Chemistry and paths for the development of this knowledge, can collaborate to legitimize the professional knowledge of the chemistry teacher, which, among others, influence the professionalization of the teaching career and the social recognition of the teaching career.